New and Evolving Management Paradigms for Hepatitis C after Liver Transplantation - Barritt, A. Sidney (2011)
Hepatitis-C induced liver failure is the leading indication for liver transplantation in the United States, and the burden of hepatitis C virus (HCV)-induced liver disease is not expected to peak for at least another decade. 2011 will usher in a new era of directly acting antiviral therapies and personalized medicine that will assist patients and clinicians in choosing the best drug regimen. Specific markers to predict sustained virologic response (SVR) in the posttransplant setting are under development, and the role of graft genetic markers like interleukin-28B and interferon-γ inducible protein-10 have yet to be fully defined. Lessons and experiences from treating the pretransplant population will be applied to patients with recurrent posttransplant HCV while studies specific to this population proceed. New paradigms for HCV treatment give promise to reducing the pretransplant burden of disease and improving SVR rates in the posttransplant population.